The Influence of DER and CR on EVA at PT Adhi Karya (Persero), Tbk from 2012 to 2022 - Dianti, Selvi (Indonesian Financial Review, 2023)
The purpose of this research is to find out how much influence DER and CR have on EVA at PT. Adhi Karya (Persero) Tbk. partially and simultaneously. The population and sample data used in this research are financial report data in the form of balance sheets and profit and loss at PT. Adhi Karya (Persero) Tbk for the period 2012 to 2022. The research methodology used is a quantitative descriptive analysis method. The data used is secondary data. Hypothesis testing is carried out using the F test and t test. with a significance level (?) of 5%. Data analysis used statistical data processing software, namely EVIEWS version 12. The results of the study showed that partially the DER) did not have a significant effect on EVA but the CR has no significant effect on EVA. Simultaneously, DER and CR have no significant effect on EVA.